Missing the boat: Australia and asylum seeker deterrence messaging - Fleay, Caroline; Cokley, J.; Dodd, A.; Briskman, L.; Schwartz, L. (Wiley-Blackwell Publishing Ltd., 2016)
© 2016 The Authors. International Migration.Many of Australia's border protection policies have focused on attempts to deter the arrival of asylum seekers by boat. These include government ‘messaging’ in the hope this will influence the decision-making of would-be boat arrivals. This article outlines the findings of an exploratory study on the sources of information accessed by asylum seekers, prior to and during their boat journeys to Australia, about their destination country. The findings suggest that government media and Internet strategies focused on deterring asylum seekers are adopted without full regard to how information is sourced before and during these boat journeys.